2018
DOI: 10.1080/10495398.2018.1448224
|View full text |Cite
|
Sign up to set email alerts
|

Varied Approach of Using MSCs for Bovine Embryo In Vitro Culture

Abstract: The objective of the present study was to evaluate the effect of porcine mesenchymal stem cells (MSCs) secreted factors on bovine in vitro embryo development using MSCs in different culture systems: SOF medium, SOF medium conditioned by MSCs in monolayer, and in reverse drop and by embryo culture in coculture with MSCs. Statistically highly significant differences were noted between the number of blastocysts derived cultures in all tested culture systems. The in vitro culture in SOF turned out to be the most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…At present, there are few studies on the association between SNP of GH , GHR, and GHRHR with sheep growth traits, and only one breed of sheep was tested and analyzed [ 18 , 19 , 20 , 21 , 22 , 41 , 42 ]. The association between InDel of GH and sheep growth has only been reported in Luxi Blackhead sheep [ 15 ]. For the first time, this study examined the distribution of the InDel loci of the GH axis key genes in multiple breeds of Chinese sheep and the association analysis with different population growth traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are few studies on the association between SNP of GH , GHR, and GHRHR with sheep growth traits, and only one breed of sheep was tested and analyzed [ 18 , 19 , 20 , 21 , 22 , 41 , 42 ]. The association between InDel of GH and sheep growth has only been reported in Luxi Blackhead sheep [ 15 ]. For the first time, this study examined the distribution of the InDel loci of the GH axis key genes in multiple breeds of Chinese sheep and the association analysis with different population growth traits.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular marker-assisted selection plays an important role in the process of molecular breeding of beef cattle and sheep in China [ 12 , 13 , 14 ]. With the development of InDel markers located on functional genes, some InDels have been identified as functional markers related to the growth of mutton sheep [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that GEM is a regulatory protein that participates in receptor-mediated signal transduction at the plasma membrane ( Maguire et al, 1994 ). It is widely expressed in many tissues and organs, including the spleen, lung and large intestine of the goat ( Xu et al, 2018 ), and it is overexpressed in skeletal muscle in individuals with type 2 diabetes ( Maguire et al, 1994 ). Here, we propose that the expression of GEM in the eye might also be clinically significant in glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…(24) Coculture has in this way been found to increase the efficiency of Bovine in vitro embryo culture. (25) ] A2 -Oxygen availability (7 studies). Six studies evaluated the effect of oxygen (O 2 ) availability, and one additional study analyzed the effect of nitric oxide (NO) concentration on embryo production.…”
Section: General Characteristics Of the Sources Of Evidencementioning
confidence: 99%